2000
DOI: 10.1177/00220345000790111001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Variation of Stimulated Salivary Flow Rates

Abstract: Salivary hypofunction is associated with oral and pharyngeal disorders and requires early diagnosis and intervention. Large variability in salivary flow rates within and between individuals has been reported, which has impaired the establishment of standard values. The objective of this study was to determine variations in stimulated parotid and submandibular flow rates over 6 hours and to define salivary hypofunction. Pooled mean, standard deviation, and coefficient of variation values for four collection tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 30 publications
7
69
2
2
Order By: Relevance
“…UWS and SWS are both outcomes of interest. However, it is important to realize that patients show substantial intra-individual variability in salivary flow, resulting in a large standard deviation [40,41]. Therefore, adequate sample sizes are needed to show the effect of treatment on salivary gland function.…”
Section: Effects On Exocrine Gland Function and Sicca Symptomsmentioning
confidence: 99%
“…UWS and SWS are both outcomes of interest. However, it is important to realize that patients show substantial intra-individual variability in salivary flow, resulting in a large standard deviation [40,41]. Therefore, adequate sample sizes are needed to show the effect of treatment on salivary gland function.…”
Section: Effects On Exocrine Gland Function and Sicca Symptomsmentioning
confidence: 99%
“…Recently, a variation of 27%-44% was reported to be present for SFRs over time (27). Accordingly, a 45% range in stimulated parotid and submandibular SFRs was noted to be a normal variation, and values less than 45% were suggested to define salivary hypofunction (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a variation of 27%-44% was reported to be present for SFRs over time (27). Accordingly, a 45% range in stimulated parotid and submandibular SFRs was noted to be a normal variation, and values less than 45% were suggested to define salivary hypofunction (27). Therefore, the diagnosis and assessment of salivary hypofunction are relatively subjective, unless an individual base record of salivary flow has been established (14).…”
Section: Discussionmentioning
confidence: 99%
“…Salivary flow has been reported to both decrease [10,11] and not decrease with age [12,13]. An epidemiological survey in Europe and America found that approximately 25% of the population was aware of xerostomia or dry mouth syndrome [14], while in Japan, an estimated 8million to 30 million patients are known to be unaware [15].…”
Section: Introductionmentioning
confidence: 99%